Interviews - Soderbergh, Steven 1963-; Kaufman, Anthony (Conversations with filmmakers series, 2015)
"The long and prolific career of Steven Soderbergh (b. 1963) defies easy categorization. From his breakout beginnings in 1989 with sex, lies, and videotape to 2013, when he retired from big-screen movie-making to focus on other pursuits including television, the director's output resembles nothing less than an elaborate experiment. Soderbergh's Hollywood vehicles such as the Ocean's Eleven movies, Contagion, and Magic Mike appear alongside risky, unconventional, outside-the-box, and low-budget exercises such as Schizopolis, Bubble, and The Girlfriend ExperienceThis updated edition details key career moments: his creative crisis surrounding his fourth film, The Underneath; his rejuvenation with the ultra-low-budget free-style Schizopolis; the mainstream achievements Erin Brockovich, Traffic, and the Ocean's Eleven films; and his continuing dedication to pushing his craft forward with films as diverse as conspiracy thrillers, sexy dramas, and biopics on Che Guevera and Liberace.Spanning twenty-five years, these conversations reveal Soderbergh to be as self-effacing and lighthearted in his later more established years as he was when just beginning to make movies. He comes across as a man undaunted by the glitz and power of Hollywood, remaining, above all, a truly independent filmmaker unafraid to get his hands dirty and pick up the camera himself"..